Місце та значення АПК в територіальній організації національної економіки - Добровольська, Олена Володимирівна; Dobrovolska, Olena; Халатур, Світлана Миколаївна; Khalatur, Svetlana (Західнодонбаський інститут економіки і управління, 2012)
У статті розглянуто значення АПК в територіальній організації національної економіки, як чинник формування системи економічної безпеки держави. Висвітлені цілі структурної перебудови економіки України. Наведені й проаналізовані дані рослинництва й тваринництва в Україні та їх значення для сталого розвитку сільськогосподарського комплексу. The article considers the value of agriculture in the territorial organization of the national economy, as a factor in the formation of the economic system security of the state. The goals of the structural adjustment of the Ukrainian economy are highlighted. The given data and analysis of crop and livestock data in Ukraine and their importance for the sustainable development of the agricultural complex are presented and analyzed.
The place and meaning of agroindustrial complex in the territorial organization of the national economy
Keywords: національна економіка; national economy; агропромисловий комплекс; agro-industrial complex; інфраструктура економіки; economy infrastructure; продовольчий сектор; food sector